Strengthening Civic Character through Community Service Based on Digital Local Wisdom - Iswara Gandhi; Rani Nuraeni; Anthony Rodriguez; Tiurida Lily Anita; Rosa Lesmana (ADI Publisher, 2025)
The digital era, marked by disruption and globalization, poses challenges to strengthening civic character, particularly in preserving values of mutual cooperation, social responsibility, and environmental awareness, with universities playing a strategic role through community service programs rooted in local wisdom and digital adaptation. This community service aims to analyze the effectiveness of the Digital-Based Environmentally Concerned Village program in strengthening civic character among the people of Sumberjaya Village, Sukabumi. The program was implemented in a rural agrarian village community, where most residents work as farmers and small traders. The community strongly upholds traditions of collective work and environmental care, such as joint land cleaning and deliberation meetings. These practices were contextualized into digital initiatives to encourage broader participation. A qualitative case study approach was employed through participatory observation, in-depth interviews with students, residents, and local leaders, and analysis of documents and digital artifacts produced during program implementation. The findings indicate increased nationalism and patriotism through the internalization of local values, the development of digital ethics and social responsibility in media use, enhanced collaboration and mutual cooperation, and greater environmental concern, with the integration of local wisdom and digital technology serving as a key catalyst that expanded program reach and participation. The synergy between tradition and digital innovation is an effective strategy to foster adaptive, caring, and empowered citizens, and it can be replicated in other communities with adjustments to their respective local wisdom.